Effective stacking and transplantation of stem cell sheets using exogenous ROS-producing film for accelerated wound healing. (1st September 2019) - Koo, Min-Ah; Hee Hong, Seung; Hee Lee, Mi; Kwon, Byeong-Ju; Mi Seon, Gyeung; Sung Kim, Min; Kim, Dohyun; Chang Nam, Ki; Park, Jong-Chul
Graphical abstract: Abstract: Extensive skin loss caused by burns or diabetic ulcers may lead to major disability or even death. Therefore, cell-based therapies that enhance skin regeneration are clinically needed. Previous approaches have been applied the injections of cell suspensions and the implantation of biodegradable three-dimensional scaffolds seeded cells. However, these treatments have limits due to poor localization of the injected cells and insufficient delivery of oxygen and nutrients to cells. Recently, cell sheet-based tissue engineering has been developed to transplant cell sheets, which are cell-dense tissues without scaffolds. Because cell density is one of the important factors for improving the therapeutic effect of cell transplantation, transplanting layered cell sheet constructs can promote the recovery of tissue function and tissue regeneration compared with a single cell sheet. Thus, this study designed ROS-induced cell sheet stacking method with newly fabricated hematoporphyrin-incorporated polyketone film (Hp-PK film) to enhance cell sheet delivery efficiency and application in wound healing. We have demonstrated the therapeutic effect of a multi-layered mesenchymal stem cell sheets onto a full-thickness wound defect in nude mice. Consequentially, three-layered cell sheets transplanted and stacked by ROS-induced method promoted angiogenesis and skin regeneration at the wound site. Thus, our strategy based on Hp-PK film, which allows for easy stacking and transplantation of cell sheets, could be applied to enhance tissue regeneration. Statement of Significance: We herein report exogenous ROS-induced cell sheet stacking method with newly fabricated hematoporphyrin-incorporated polyketone film (Hp-PK film) to enhance cell sheet transplantation efficiency and application in wound healing. Although there are several ways to stack-up cell sheets, all of these methods have limitations in transplanting the cell sheet directly to the target site. The method is simple and takes a relatively short time compared to previously reported methods for stacking and transplanting cell sheets. Thus, our study will provide a scientific impact because the method of applying exogenous ROS generated from Hp-PK film on cell detachment can transplant the cell sheet through a process of putting a cell sheet-cultured film on the lesion, irradiating with light, and then removing only the film.